Development and Evaluation of an Educational Program for Community Pharmacists on Cardiovascular Risk Assessment - Monica Zolezzi (10115698) (2020)
Purpose Cardiovascular disease (CVD) risk assessment is an important strategy for the prevention of CVD. Pharmacists play an important role in CVD risk assessment and management (CVDRAM). Our previous study identified gaps in knowledge among community pharmacists for the provision of CVDRAM services as assessed through patient simulation. Therefore, our objectives were: a) to develop and evaluate an educational program on CVD risk assessment for community pharmacists, b) to assess the knowledge and skills of participating pharmacists in assessing and managing CVD risk before and after enrolling in the educational program and c) to explore pharmacists’ satisfaction and perceived effectiveness of the educational program. Methods Using a blended learning instructional approach, the educational program for a subset of 25 community pharmacists recruited from our previous study consisted of two face-to-face workshops, and an online 5-module course on CVD risk factors such as hyperlipidemia, hypertension, diabetes, obesity, and smoking cessation based on principles of adult learning. A repeated measures study design was utilized by measuring participants’ knowledge on pre- and post-questionnaires and an objective structured clinical examination (OSCE) at the conclusion of the educational program was also used to assess its impact on the knowledge and skills of community pharmacists in the provision of CVD risk assessment and management (CVDRAM) services. The knowledge questionnaire was completed by 23 pharmacists while the OSCE was completed by 8 pharmacists. In addition, a survey assessed the pharmacists’ level of satisfaction with the educational program. Results At the conclusion of the educational program, the participating pharmacists achieved knowledge and skills for the provision of CVDRAM services. Knowledge scores in relation to CVDRAM significantly improved after the educational program [out of a maximum of 20 points, the median (interquartile range) = 9 (7– 9) at pre- vs 12 (12– 13) at post-educational program], p< 0.001. On the OSCE, the median (interquartile range) scores for Stations 1 and 2 were 66 (63– 71) and 71 (67– 76), respectively. Out of the 21 pharmacists that completed the satisfaction survey, 71% were very satisfied and 29% were satisfied with the educational program. Conclusion The educational program improved pharmacists’ knowledge and skills for the provision of CVDRAM services. Other Information Published in: Risk Management and Healthcare Policy License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.2147/rmhp.s231075